Challenges of Administering COVID-19 Vaccine in Some Selected States of Northeast Nigeria - Sambo, Usman; Ibrahim, Suleiman; Mohammed, Musa (Journal of Current Social and Political Issues, 2023)
The COVID-19 pandemic has successfully registered itself among the league of global epidemics that the world is currently battling. The virus, which emerged in December 2019 in China, quickly spread worldwide, paralysing socioeconomic, political, and cultural activities around the globe. Nigeria is one of the African countries that is most affected by the COVID-19 pandemic, especially socioeconomically and politically. Although the pattern of spread in the country indicates a higher incidence in the South than in Northern Nigeria, some factors made the case in Northern Nigeria an interesting study. The study is an examination of the challenges that influenced the process of administering the COVID-19 vaccine in Northeast Nigeria. The study used a quantitative phenomenological study as a methodology. Data were collected from selected informants with relevant and valuable information on the subject matter in the area of study. The data obtained were analysed and interpreted using content analysis. Culture, religion, and perception, in addition to the attitude of the political class, all contributed to the negative perception of COVID-19 as a pandemic and its vaccine as a preventive measure. Most of the inhabitants of Northeast Nigeria are found to have harboured negative thoughts against the Virus and its vaccination because of some reported cases of side effects and the way the politicians turned the pandemic into a racket of money-making. The study recommends, among others, that royal fathers, religious clerics, and opinion moulders should be rigorously engaged in a massive campaign to disabuse all negative perceptions and to convince the populace on safety and prevention.